Late Paracetamol Therapy for Hemodynamically Significant Patent Ductus Arteriosus in Very Low Birth Weight Infants Born before 28+6 Weeks Gestation – Echocardiographic and Clinical Correlation - Gopagondanahalli, Krishna Revanna; Chandran, Suresh; Mittal, Rashmi Arun; Ang, Wai Lin; Hashim, Eman Awad A; Rajadurai, Victor Samuel; Haium, Abdul Alim Abdul (Archives of Clinical and Medical Case Reports, 2021)
Aim: To ascertain the efficacy of late paracetamol therapy in managing haemodynamically significant patent ductus arteriosus (hsPDA) in very low birth weight (VLBW) infants and correlate echocardiographic findings with clinical outcome. Methods: This is a retrospective audit of 23 VLBW infants (< 28+6 weeks) born in a large tertiary hospital who received late paracetamol therapy (initiated beyond two weeks of life) for hsPDA. Baseline patient characteristics, echocardiographic data before and after treatment, and adverse effects were collected and analyzed. Results: The mean gestation was 26.1 ± 2.1 weeks and birth weight 830 ± 307 grams. The mean age at initiation of paracetamol therapy was 31 ± 2.9 weeks postmenstrual age (IQR range 28-33 weeks). A significant decrease in PDA size was noted (2.82 ± 0.72 mm pre-treatment to 2.50 ± 0.59 mm post-treatment, p = 0.03). The maximal systolic and diastolic velocity across PDA, before and after paracetamol therapy was also significantly different (2.23 ± 0.83 m/s vs. 2.68 ± 0.77 m/s, p = 0.04 and 0.63 ± 0.45 m/s vs. 1.06 ± 0.63 m/s, p < 0.01, respectively). However, the overall complete closure rate of hsPDA was only 13% (3 out of 23), and the constriction rate (decrease in size by more than 25%) was 18%. There were no significant side effects. Conclusion: Late therapy with paracetamol appears to have a modest effect on reducing the size of hsPDA in VLBW infants, but the absolute closure rate is low. It could still be considered before surgical ligation of the PDA.